Simultaneous integrated boost by intensity modulated radiation therapy in carcinoma left breast after breast conservation surgery -A preliminary experience - Agrawal, Rashi; Singh, Dinesh (International Journal of Applied Sciences and Biotechnology, 2013)
Aim of study-Breast conservation surgery followed by radiotherapy has become the standard of care for early breast cancer. Total treatment time extends from6½ to 7 weeks. In radiotherapy such a long treatment duration is always worrisome. Simultaneous treatment of cavity and breast can reduce treatment time but we should consider acute and late toxicities. Materials and methods- In this study we are presenting data of 14consecutive patients of carcinoma left breast which were treated between March 2010 and June 2012.Dose prescribed to clinical target volume breast was 50 Gy in 25 fractions and CTV boost was 60 Gy in 25 fractions. Results-Clinical target volume for cavity ranged from 34.81cc to 369.8cc. Two patients (14.2%) had acute grade 2 skin toxicity and all other (85.7%) grade 1. Higher dose in boost region did not produce differential fibrosis or edema of breast. Median follow up is 26 months. None of our patients has experienced cardiac or pulmonary toxicity till date and all are in regular follow up. Conclusion-With simultaneous integrated boost in carcinoma breast patients, overall treatment time can be reduced without increasing early and late toxicities. Accrual of more patients is continuing. DOI: http://dx.doi.org/10.3126/ijasbt.v1i4.8794 Int J Appl Sci Biotechnol, Vol. 1(4): 197-201